PROBLEM MINORITAS DALAM PERSPEKTIF AL-QUR’AN - Shomad, Bukhari Abdul (Analisis: Jurnal Studi Keislaman, 2012)
Islam, more specifically, the Koran as its   original source, has infrequently  been  made  a scapegoat  in a number  of religious  and ethnicity contained-humanitarian  issues. This paper aims at tracing the Qur’anic  paradigm  of majority-minority  relations  in public  life which is heterogeneous.  By the use of humanistic  hermeneutics,  the author  affirms the existence  of Islam  as a humanistic  religion  that upholds human rights and dictates the minority-majority  relations set up in a frame of ummatan wasat}an. The author analyzes   the terms of human being in the language of the Koran, namely: al-insa>n, al- basyar and an-na>s which all shows the meaning of human equality in general, and furthermore,  protection of their individuals and   social rights in the frame of rah}matan lil ‘a>lami>n . According to the author, the term majority-minority  is a new concern in Islam. In the context of  community  of  religious  diversity,  Islam  introduced  the  concept of “People  of the Book”  regardless  of whether  or not non-Muslim religious groups are in the position of minority or majority. The term Ahl az\-Z|immah used to refer to non-Muslim communities living under Islamic government  can not also be equated with the term minority. The word “z\immi” which means those under protection denotes their assurance of security and  safety; hence  this could not be  interpreted as “helpless” or “inferiority”.